Prevalence of gingival recession in dentistry students (2017-2018) - Fahimeh Mirzaali; Amirreza Ahmadinia; Gholamreza Roshandel (مجله دانشگاه علوم پزشکی گرگان, 2019)
Background and Objective: Gingival recession is a common disease leads to esthetic problems, increased sensitivity of teeth and root caries. This study was done to determine the prevalence of gingival recession in dental students with high level of oral hygiene. Methods: This descriptive-analytic study was performed on 214 dental students of Golestan University of Medical Sciences, Gorgan, Iran during 2017-2018. After collecting demographic information, clinical examination including Oral Hygiene Index (OHI) and Gingival Index (GI), Severity of gingival recession, width of keratinized gingival, attachment of frenulum, toothbrush trauma, tooth malpositions, periodontal diseases and other iatrogenic factors was measured. Results: Prevalence of gingival recession was 23.8% .Class 1 and 2 of gingival recession was 84.62 % and 15.38%, respectively. Class 3 and 4 of gingival recession did not observe in any subjects. Toothbrush trauma was the most etiologic factor in 35.4% of dental students suffering of gingival recession (P<0.05). Also, dental malposition with 20.83%, loss of keratinized gingival with 14.58%, orthodontics procedures with 12.5%, periodontal diseases with 10.4% were the other factors in gingival recession. Conclusion: Toothbrush trauma and dental malposition are the most important etiologic factors in dentistry students suffering from gingival recession.